2016
DOI: 10.1103/physrevlett.117.192001
|View full text |Cite
|
Sign up to set email alerts
|

Testing Hadronic Interactions at Ultrahigh Energies with Air Showers Measured by the Pierre Auger Observatory

Abstract: Ultrahigh energy cosmic ray air showers probe particle physics at energies beyond the reach of accelerators. Here we introduce a new method to test hadronic interaction models without relying on the absolute energy calibration, and apply it to events with primary energy 6-16 EeV (ECM = 110-170 TeV), whose longitudinal development and lateral distribution were simultaneously measured by the Pierre Auger Observatory. The average hadronic shower is 1.33±0.16 (1.61±0.21) times larger than predicted using the leadi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
171
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 208 publications
(194 citation statements)
references
References 32 publications
14
171
0
3
Order By: Relevance
“…Three different experiments studied the muon deficit in an energy range which overlaps with the one of this work: First, the Pierre Auger Observatory reported a muon deficit of 30 % to 80 % in the mixed composition scenarios [11,13]. Second, the Telescope Array Collaboration observed a deficit of ∼ 67 % against proton-induced QGSJetII-04 simulations, the latter being in agreement with the composition derived from their X max measurements [12].…”
Section: Introductionsupporting
confidence: 79%
“…Three different experiments studied the muon deficit in an energy range which overlaps with the one of this work: First, the Pierre Auger Observatory reported a muon deficit of 30 % to 80 % in the mixed composition scenarios [11,13]. Second, the Telescope Array Collaboration observed a deficit of ∼ 67 % against proton-induced QGSJetII-04 simulations, the latter being in agreement with the composition derived from their X max measurements [12].…”
Section: Introductionsupporting
confidence: 79%
“…However, there is mounting evidence that a e-mail: michael.unger@kit.edu current hadronic interaction models do not provide a satisfactory description of the muon production in air showers and that there is a deficit in the number of muons predicted at the ground level by the models when compared to the air shower measurements (see Refs. [6][7][8][9][10]). …”
Section: Introductionmentioning
confidence: 99%
“…The number of muons in the Auger data is also larger than the MC prediction for iron. In addition to that, the Auger group reported that the observed hadronic signal in UHECR air showers is 1.61 ± 0.21(1.33 ± 0.16) times larger than the MC prediction values for QGSJET II-04 [6] (EPOS-LHC [7]) model, including statistical and systematic errors [8]. Thus, the Auger group claimed the excess of muons in the data.…”
Section: Introductionmentioning
confidence: 92%